Inhibition and anticipation in visual search: evidence from effects of color foreknowledge on preview search. - Braithwaite, J; Humphreys, G (2003)
We present four experiments in which we examined the effects of color mixing and prior target color knowledge on preview search (Watson and Humphreys, 1997). The task was to detect a target letter (an N or a Z) that appeared along with other new letters, when old distractors remained in the visual field. In some conditions, participants were told the target's color, in others, they were not. Foreknowledge of the target's color produced large improvements in search for both baseline and preview presentations (Experiment 1). For preview presentations, the magnitude of this effect was reduced if the target shared its color with a single colored set of previewed letters (Experiment 2). Removing this similarity across the displays greatly improved search efficiency (Experiment 3). In Experiment 4, we assessed and rejected the proposal that the effects reflected the probability that the target was carried by a particular color. We discuss the results in terms of separate effects of (1) inhibitory carryover from a preview color group and (2) an anticipatory set for a known target color.